2010
DOI: 10.1007/s11356-010-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pb, Cd, Cu, Zn, and Ni to titanium dioxide nanoparticles: effect of particle size, solid concentration, and exhaustion

Abstract: Comparison of K (d), distribution coefficient, with other literature showed that the nanoparticles were better sorbents than other metal oxide nanoparticles and a commercial activated carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
74
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(84 citation statements)
references
References 22 publications
4
74
0
1
Order By: Relevance
“…Adsorption is the most preferred method for removal of heavy metals from aqueous solutions due to its simplicity and its high A. T. Sdiri (&) Á T. Higashi Faculty of Life and Environmental Sciences, University of Tsukuba, 1-1-1 Tennodai, Tsukuba 305-8572, Japan e-mail: alisdiri@yahoo.fr effectiveness (Sdiri et al 2011(Sdiri et al , 2012a. In this regards, multiple researchers studied the effectiveness of various type of clay in removing heavy metals from aqueous solutions including kaolinite (Sari et al 2007;Schaller et al 2009), bentonite (Ulmanu et al 2003;Kaya and Hakan Ö ren 2005;Eren et al 2009), illite (Ozdes et al 2011), sepiolite (Guerra et al 2010), montmorillonite (Lin and Juang 2002), and other adsorbents (Al-Degs et al 2006;Engates and Shipley 2011). Many other studies have been undertaken to evaluate the adsorptive capacity of various bioadsorbents in the removal of inorganic pollutants (Ahmad et al 2010;Das 2012;Dubey and Shiwani 2012;Revathi et al 2012;Eren 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is the most preferred method for removal of heavy metals from aqueous solutions due to its simplicity and its high A. T. Sdiri (&) Á T. Higashi Faculty of Life and Environmental Sciences, University of Tsukuba, 1-1-1 Tennodai, Tsukuba 305-8572, Japan e-mail: alisdiri@yahoo.fr effectiveness (Sdiri et al 2011(Sdiri et al , 2012a. In this regards, multiple researchers studied the effectiveness of various type of clay in removing heavy metals from aqueous solutions including kaolinite (Sari et al 2007;Schaller et al 2009), bentonite (Ulmanu et al 2003;Kaya and Hakan Ö ren 2005;Eren et al 2009), illite (Ozdes et al 2011), sepiolite (Guerra et al 2010), montmorillonite (Lin and Juang 2002), and other adsorbents (Al-Degs et al 2006;Engates and Shipley 2011). Many other studies have been undertaken to evaluate the adsorptive capacity of various bioadsorbents in the removal of inorganic pollutants (Ahmad et al 2010;Das 2012;Dubey and Shiwani 2012;Revathi et al 2012;Eren 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that the process conditions such as pH, the amount of clinoptilolite and the amount of nickel in the initial solution, have a large effect on the metal removal efficiency. Engates and others (Engates and Shipley 2011) performed studies concerning adsorption of nickel(II), cadmium(II) and lead(II) ions onto TiO 2 nanoparticles. The results confirmed a significant adsorption capacity of titanium dioxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these adsorbents have been used on a large scale to improve the capacity of adsorption of compounds with specific functional groups [11]. Nanoscale metal oxides have the potential to save water treatment costs and given their size and high absorption efficiency, they can improve the efficiency of technologies [12,13].…”
Section: Introductionmentioning
confidence: 99%